Relações socioecológicas na construção das paisagens étnicas ucranianas na região Centro-Sul do Paraná (1890-1945) (TEL Tempo, Espaço e Linguagem, 2022)
The present paper aims to reflect on the forms of transformation and re-signification of socio-ecological relations during the process of immigration of Ukrainians to Paraná. To this end, we analyze narrative sources of individuals who settled in the state between the years 1890 and 1945. We highlight in these accounts the relations of this group with the landscape and the environment.